2015
DOI: 10.1097/pgp.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Ependymoma With Clinical Response to GnRH Analog Therapy

Abstract: Summary Extraneural ependymomas are rare tumors that occur in sacrococcygeal, pelvic and extra pelvic regions. While sacrococcygeal extraneural ependymomas are equally distributed among males and females, pelvic and extra pelvic ependymomas have been exclusively reported in women, mainly of child bearing age. We present a case of extraneural, pelvic ependymoma that showed clinical response to GnRH therapy with its immunohistochemical and electron microscopic analysis, and an overview of primary extraneural epe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…CD99 and S100 are more commonly positive in CNS ependymomas than in their extraneural counterparts 6 . This immunophenotype stated by Idowu, is present in all published cases of EnE 3,4,5 , and it confirms the hypothesis that EnE arise by different mechanisms from their CNS counterparts 6 . However, it appears that EnE arising in different place or mechanism, show different immunoprofile.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…CD99 and S100 are more commonly positive in CNS ependymomas than in their extraneural counterparts 6 . This immunophenotype stated by Idowu, is present in all published cases of EnE 3,4,5 , and it confirms the hypothesis that EnE arise by different mechanisms from their CNS counterparts 6 . However, it appears that EnE arising in different place or mechanism, show different immunoprofile.…”
Section: Discussionsupporting
confidence: 78%
“…While sacrococcygeal ependymomas are equally distributed among males and females, paraovarian pelvic and extra pelvic ependymomas have been exclusively reported in women, mainly of child bearing age 1,3 . However, there was a case of a 75-year-old patient with pelvic EnE 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addtion, a case of ovarian ependymoma responding to gonadotropin-releasing hormone(GnRH) therapy was reported by Fang et al in 2015, in which a 30-yr-old female with a large pelvic ependymoma who was treated with presurgical GnRH analogue therapy and fertility-sparing surgical resection remained disease-free after over 30 months without post-surgical treatment [ 17 ]. Similarly, some studies have demonstrated the role of anti-oestrogens in the treatment of ovarian ependymoma.…”
Section: Discussionmentioning
confidence: 99%